Independent Water Consumer Protection Ciapus Village Through Bandung Regency Government Supervision of Independent Water Management - Dasuki Suhardini, Eni (Greenation Research & Yayasan Global Resarch National, 2024)
Water is a natural resource that humans need as a source of livelihood and shelter. Business actors address this as a way to earn income. However, the methods used do not or do not have permits by the terms and procedures specified in the statutory regulations. One of them is the independent water management business actor in Ciapus Village, which of course, this situation has attracted the interest of researchers to research how to protect consumers and producers/independent water management business actors and what the government's responsibility is regarding this situation and preserving the environment in Ciapus Village, Banjaran District, Regency. Bandung. To get answers to these problems, researchers used an empirical juridical approach, descriptive analysis research specifications, document study data collection techniques to obtain secondary data, and field studies to obtain primary data bymeans of observation and interviews. Based on the results of research in the Ciapus Village area, Banjaran District, it was found that independent water companies managed by individuals [3 entrepreneurs] do not yet have permits, but those managed by Bumdes Raksa Manggala have establishment permits, and business permits, and certificates of drinking water product test results from Bandung District Health Service Laboratory. The Regional Government of Bandung Regency has not yet supervised independent water management, so that independent water management entrepreneurs can take as much water as possible from their springs, without paying attention to environmental sustainability. This results in when the dry season arrives, the water flow decreases and even dries up.